Comparing the views of young football players and their coaches on leading behavior - Yagci, E.; Burgul, N.; Bozkurt, Ö.; Uluöz, T. (International Journal of Applied Exercise Physiology, 2021)
In the research, the opinions of young footballers were analyzed regarding to the educative and supportive, democratic, social support, autocratic and positive feedback leader behaviors received from their coaches. The demographic characteristics of footballers and coaches were examined. Leader behavior characteristics experienced by coaches were determined and included in the study, also the relationship between the demographic characteristics of football players and leader behavior characteristics experienced by coaches was studied. The data includes the TRNC A2 Super League footballers (total 126) and coaches from 7 different teams located in Nicosia.